Solitary Waves Across Supercritical Quasi‐Perpendicular Shocks. Issue 12 (20th June 2018) - Vasko, I. Y.; Mozer, F. S.; Krasnoselskikh, V. V.; Artemyev, A. V.; Agapitov, O. V.; Bale, S. D.; Avanov, L.; Ergun, R.; Giles, B.; Lindqvist, P.‐A.; Russell, C. T.; Strangeway, R.; et al.
Abstract: We consider intense electrostatic solitary waves (ESW) observed in a supercritical quasi‐perpendicular Earth's bow shock crossing by the Magnetospheric Multiscale Mission. The ESW have spatial scales of a few tens of meters (a few Debye lengths) and propagate oblique to a local quasi‐static magnetic field with velocities from a few tens to a few hundred kilometers per second in the spacecraft frame. Because the ESW spatial scales are comparable to the separation between voltage‐sensitive probes, correction factors are used to compute the ESW electric fields. The ESW have electric fields with amplitudes exceeding 600 mV/m (oriented oblique to the local magnetic field) and negative electrostatic potentials with amplitudes of a few tenths of the electron temperature. The negative electrostatic potentials indicate that the ESW are not electron phase space holes, while interpretation in terms of ions phase space holes is also questionable. Whatever is their nature, we show that due to the oblique electric field orientation the ESW are capable of efficient pitch‐angle scattering and isotropization of thermal electrons. Due to the negative electrostatic potentials the ESW Fermi reflects a significant fraction of the thermal electrons streaming from upstream (downstream) back to upstream (downstream) region, thereby affecting the shock dynamics. The role of the ESW in electron heating is discussed. Plain Language Summary: Processes governing electron thermalization across shock waves are not entirely understood. The high resolution particle and 3‐D electric field measurements provided by the Magnetospheric Multiscale Mission make it possible to study the Earth's bow shock that is an excellent laboratory for addressing the electron thermalization across supercritical shock waves. Previous observations showed that electron heating across the bow shock is generally governed by macroscopic cross‐shock electrostatic field. On the other hand, the role of the turbulence observed across the bow shock in the electron thermalization has remained unclear. In this letter we consider a particular bow shock crossing by the Magnetospheric Multiscale Mission and focus on the role of the high amplitude electrostatic solitary waves in the electron thermalization process. We accurately estimate the electrostatic solitary wave parameters and show that due to electric fields oriented oblique to a local DC magnetic field and negative electrostatic potentials with amplitudes of a few tenths of the electron temperature, these Debye‐scale structures are capable of efficient pitch angle scattering, Fermi reflection, and isotropization of thermal electrons. Key Points: Electrostatic solitary waves (ESW) across the bow shock are Debye‐scale structures with electric field oriented oblique to magnetic field ESW have negative electrostatic potential (they are not electron phase space holes) with amplitude of a few tenths of electron temperature ESW are capable of efficient pitch angle scattering, Fermi reflection, and isotropization of thermal electrons